LICENCIATURAS EM CIÊNCIAS BIOLÓGICAS NOS INSTITUTOS FEDERAIS DE EDUCAÇÃO, CIÊNCIA E TECNOLOGIA E O ENSINO MÉDIO INTEGRADO | Undergraduate in biological sciences in Institutes of Federal Education, Science and Technology and education integrated to... (Trabalho & Educação, 2016)
This research aims to contribute to the understanding on teaching education programs in Biological science offered by Federal Institutes of Minas Gerais, if they are forming the teacher to work in vocational education integrated to academic high school, which is named here as integrated education, on the perspective of integral human formation, and how this perspective of formation is contemplated in the political-pedagogical projects and curricula of these programs. The procedures and devices of data collecting, consisted in analysis of the political-pedagogical projects and curriculum matrices of the referred programs and semi-structured interviews with coordinators and teachers. The documents of eight programs were analyzed and the interviews were realized with subjects...___ Esta pesquisa teve por objetivo compreender se os Institutos Federais mineiros em seus cursos de Licenciatura em Ciências Biológicas estão formando o professor para atuar no ensino médio integrado na perspectiva da formação humana integral, e como essa perspectiva de formação é contemplada nos projetos políticos-pedagógicos e currículos dos referidos cursos. Os procedimentos e instrumentos de coleta de dados consistiram em análise dos projetos políticos-pedagógicos e matrizes curriculares dos referidos cursos e entrevistas semiestruturadas com coordenadores e professores dos mesmos. Foram analisados os documentos de oito cursos e as entrevistas foram realizadas com sujeitos...